Imogolite-Like Family - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N (Elsevier B.V., 2016)
The term nanotechnology can be defined as the science responsible for designing, manufacturing and exploiting matter on the nanometer scale. It seeks to explain and understand the relationship between structure, composition and physical properties, which may depart significantly from what bulk matter permits. In this context, imogolite can be considered an exceptional nanotube model. Using different and simple steps during imogolite synthesis, it is possible to partially or totally replace its constituting elements and significantly modify its shape while keeping the same local structure. This exceptional versatility in structure and composition makes imogolite not only a unique material but also a whole family of nanoparticles sharing the same original local structure. This chapter describes the different methods that can be used to obtain imogolite family members. The methods of syntheses, formation mechanisms and properties are also described in detail for some of the most studied imogolite varieties. © 2016 Elsevier Ltd